Sanja Kuning Phenomenon in Students’ Worksheets to Train Science Process Skills - Nur Aina; Nur Aina; Mastuang Mastuang; Mastuang Mastuang; Dewi Dewantara; Dewi Dewantara; Mazlena Binti Murshed; Mazlena Binti Murshed (Universitas Lambung Mangkurat, 2024)
Integrating local wisdom is important in learning, especially in the students' worksheet, a reference for student learning. The phenomenon of sanja kuning is very memorable for the people of South Kalimantan, with its various mythologies. This will be interesting if discussed through physics learning to support students’ science process skills. This study aims to analyze the effect of students’ worksheets integrated with local wisdom, namely the sanja kuning phenomenon, and the effectiveness of learning and improving students' science process skills. This quasi-experimental study applies students' worksheets integrated with local wisdom, namely the sanja kuning phenomenon. Data were obtained through one group pretest-posttest design with a total sample of 28 people. Data were analyzed using N-gain, and student learning outcomes obtained a gain of 0.38 with medium criteria. The data were also analyzed using a paired t-test, and the results showed that there was an effect on the learning of students' worksheets integrated with local wisdom of the Sanja kuning phenomenon. The results of this study conclude that student worksheets integrated with local wisdom, namely the Sanja kuning phenomenon, affect the teaching of light waves. In addition, the effectiveness is in the medium category. This student's worksheet can be used as an alternative to learning about light waves. The weaknesses of the research show that further development of this students' worksheet is needed to be maximized to improve the students' science process skills.